Level of customer satisfaction toward building customer loyalty : a case study at Binaraya PKINK Sdn Bhd / Nurul Aida Mohd Zin - Mohd Zin, Nurul Aida (2012)
Every supplier wants to create and retain a loyal customer who engages in continued profitable business. Customer loyalty is the measure of success of the supplier in retaining a long term relationship with the customer. Thus customer loyalty is when a supplier receives the ultimate reward of efforts in interacting with the customer. Customer loyalty tends the customer to voluntarily choose a particular product against another for need. The loyalty may be product specific or it may be company specific. When a loyal customer has repetitive requirement of the same product, such customers may be described as being ‘brand loyal’. Educating loyal customers is frequently argued to be the single most important driver of organizations’ long-term performance, which can lead to increased sales and customer share, lower costs, and higher prices. The main focus for this study is to find out the level of customer satisfaction toward building customer loyalty at BINARAYA PKINK SDN.BHD. The study was carried out on a convenience sample of 201 respondents through the distribution of structured questionnaires to BINARAYA’s existing customers within the area of Pengkalan Chepa, Kota Bharu, Kelantan. The data were analyzed using SPSS through the frequencies analysis, correlation coefficient analysis and regression analysis. From the analysis, the researcher found that customer satisfaction, service quality, trust and customer relationship management (CRM) have a significant relationship with the customer loyalty. From the findings, it shows that service quality is the critical factor while trust is the least important factor. Some conclusions are provided in the research and the researcher also stated several recommendations. It is a great pleasure if BINARAYA’s management is willing to evaluate the suggestions from the respondents and the researcher